1995
DOI: 10.1002/1097-0142(19951015)76:8<1453::aid-cncr2820760824>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Spinal metastases from solid tumors. Analysis of factors affecting survival

Abstract: Background. Factors affecting survival were determined for 109 patients with thoracic spine metastases and cord compression. Lung, prostate, and breast were the most common primary sites (78%). All patients had surgical decompression of the spinal cord, and 99% received radiotherapy. Methods. Survival was determined based on anatomic site of primary carcinoma, preoperative neurologic deficit, extent of disease, number of vertebral bodies involved, tumor location (site of cord compression), and age. The respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
130
1
6

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(146 citation statements)
references
References 26 publications
5
130
1
6
Order By: Relevance
“…Because these patients were selected for surgery, their general condition was better than that of patients who were not surgical candidates. Conversely, our finding that the EOD of patients with spinal metastases is not an independent predictor of survival concurs with the results of Sioutos et al 28 Age, gender, preoperative urinary disturbance, synchronous distant metastases, and single-modality adjuvant therapy (only chemotherapy or radiotherapy) were not statistically significant prognostic parameters for our patients. Treatment of the primary tumors before surgery was not a statistically significant factor for prediction of overall survival.…”
Section: Discussionsupporting
confidence: 92%
“…Because these patients were selected for surgery, their general condition was better than that of patients who were not surgical candidates. Conversely, our finding that the EOD of patients with spinal metastases is not an independent predictor of survival concurs with the results of Sioutos et al 28 Age, gender, preoperative urinary disturbance, synchronous distant metastases, and single-modality adjuvant therapy (only chemotherapy or radiotherapy) were not statistically significant prognostic parameters for our patients. Treatment of the primary tumors before surgery was not a statistically significant factor for prediction of overall survival.…”
Section: Discussionsupporting
confidence: 92%
“…The revised Tokuhashi score is considered to be a reasonable tool for predicting the prognosis of patients' life expectancy as has been confirmed by numerous authors [8][9][10][11][12][13][14]. In a retrospective review of 246 patients, Tokuhashi and colleagues showed a predictive value of 85.3 % in the group with a score of 0-8, 73.1 % with a score of 9-11 and 95.4 % in the 12-15 group.…”
Section: Discussionmentioning
confidence: 88%
“…This improved survival following surgical intervention was also seen by Majeed et al [13] in their relatively small series of 55 patients. Surgery has a positive impact on improvement in patients' neurological status and Sioutos et al [14] demonstrated that patients who were ambulatory pre-operatively and those with only one vertebral involvement survived statistically longer than patients who were non-ambulatory and with multilevel disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several scoring systems have been proposed to assess survival prognosis for spinal metastasis after surgery or radiotherapy alone [8][9][10][11]. However, (1) the number of patients with lung cancer in those studies is very low, making it difficult to draw conclusions on this specific tumor type; (2) postoperative function outcome is not considered in all of those studies; (3) some old and commonly used scoring systems have underestimated the life expectancy of patients with spinal metastases of lung cancer due to the increased survival time for those patients in recent years [12,13].…”
Section: Introductionmentioning
confidence: 99%